Manajemen SDM Berorientasi Teknologi Informasi pada SMA Negeri 1 Ujung Batu Rokan Hulu, Riau - Puja Aulia; Irawati Irawati; Rini Setyaningsih; Edi Iskandar; Umar Faruq (Social Science Academic, 2026)
This study aims to analyze the application of information technology-based human resource management at SMA Negeri 1 Ujung Batu Rokan Hulu and identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive type of research. The research subjects consisted of school principals, heads of administration, administrative staff, teachers, and school technician operators. Data collection techniques are carried out through interviews, observations, and documentation, while data analysis uses the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that information technology-based human resource management has been implemented quite well, which includes human resource planning, competency development, increased work productivity, performance evaluation, system security, and user satisfaction. The application of information technology helps the administration management of educators and education personnel to be more effective and efficient. Factors supporting implementation include the role of school principals as the main driver, the existence of school technicians, the availability of technological devices, and the adoption of technology in school activities. Meanwhile, inhibiting factors include lack of digital training, unstable network connections, limited technological devices, as well as system security issues and application errors. The conclusion of this study shows that the implementation of information technology-based human resource management at SMA Negeri 1 Ujung Batu Rokan Hulu has gone well and has a positive impact on the effectiveness of the management of educators and education personnel, although there are still several obstacles that need to be improved to optimize the implementation of the system.